Redox flow batteries: Status and perspective towards sustainable stationary energy storage - Sánchez-Díez, Eduardo; Ventosa, Edgar; Guarnieri, Massimo; Trovò, Andrea; Flox, Cristina; Marcilla, Rebeca; Soavi, Francesca; Mazur, Petr; Aranzabe, Estibaliz; Ferret, Raquel (Journal of power sources, 2021)
Redox-flow batteries, based on their particular ability to decouple power and energy, stand as prime candidates for cost-effective stationary storage, particularly in the case of long discharges and long storage times. Integration of renewables and subsequent need for energy storage is promoting effort on the development of mature and emerging redox-flow technologies. This review aims at providing a critical analysis of redox-flow technologies that can potentially fulfill cost requirements and enable large scale storage, mainly aqueous based systems. A comprehensive overview of the status of those technologies, including advantages and weaknesses, is presented. Compiled data on the market permeability, performance and cost should serve, together with the perspective included, to understand the different strategies to reach the successful implementation, from component development to innovative designs. [Display omitted] •Redox-flow batteries are moving forward to sustainable stationary storage.•Focus for RFBs is put on durability and cost targets.•VRFBs are leading in terms of performance and market permeation.•Alternative technologies are mainly based on low-cost abundant active materials.•Membraneless and semisolid RFBs go beyond current conceptual limitations.